Radical resource productivity as an inspiration for business model innovation: The case of foodchain - Dror Etzion (Journal of Business Models (JOBM), 2020)
Radical resource productivity (RRP) is a design and engineering approach to manufacturing that can potentially yield dramatic improvements in energy and material efficiency, and thus contribute to sustainability. This study explores whether the RRP can also be a source of business model innovation in the service sector. An application of RRP in a restaurant in Montreal is presented, and analyzed by means of an activity map. The case suggests that activity maps can be employed to design business models that promote sustainability through pursuit of radical resource productivity.
Keywords: 650; radical resource productivity; business model innovation; service sector; restaurant; activity map; sustainability